VALIDATION OF CHROMATOGRAPHIC METHODS: ROBUSTNESS INVESTIGATION WITH USE OF EXPERIMENTAL DESIGN - N. A. Epshtein (Разработка и регистрация лекарственных средств, 2019)
This article covers the theoretical and practical basics of research of the robustness of chromatographic methods on the base of Plackett - Burman design. Step by step, with explanations and examples, the estimation of significant (potentially critical) factors as well as the estimation of permissible limits of the changes of factors and responses are considered. The assessment of the limits is important for the justification of the requirements to the suitability of a chromatographic system. Also, we suggest the recommendations for performing necessary calculations in Excel and for the assessment of robustness of chromatographic methods.